A Study of the Performance and Financial Reporting Practices of Philippine Government Owned and Controlled Corporations: Home Guaranty Corporation (HGC) - Cayanan, Arthur S. (Philippine Management Review; Vol 24 (2017), 2017)
This paper looked into the financial reporting practices of Home Guaranty Corporation (HGC)—being a government-owned and controlled corporation that relies on government financing and subsidy every time it goes into deficit—and assessed the adequacy of its financial disclosures as prescribed by the financial reporting standards in the Philippines. This paper also evaluated the company’s financial performance based on the information provided in the financial statements.